High-Efficiency Ho:YAP Pulse Laser Pumped at 1989 nm - Chao Niu; Yan Jiang; Ya Wen; Lu Zhao; Xinyu Chen; Chunting Wu; Tongyu Dai (Crystals, 2021)
A Tm:YAP laser with an output wavelength of 1989 nm was selected for the first time as the pump source of a Q-switched Ho:YAP laser. When the absorbed power was 30 W, an average power of 18.02 W with the pulse width of 104.2 ns acousto-optic (AO) Q-switched Ho:YAP laser was obtained at a repetition frequency of 10 kHz. The slope efficiency was 70.11%, and the optical-optical conversion efficiency was 43.03%. The output center wavelength was 2129.22 nm with the line width of 0.74 nm.